Subunits of the alkaline phosphatase of Bacillus licheniformis: chemical, physicochemical, and dissociation studies. - Hulett, F M (1976)
The alkaline phosphatase (orthophosphoric monoester phosphydrolase, EC 3.1.3.1) of Bacillus licheniformis MC14 was studied in an attempt to determine the number of subunits contained in the 120,000-molecular-weight native enzyme. Two moles of arginine was liberated per mole of native enzyme by carboxypeptidases A and B in the presence of sodium dodecyl sulfate. The effect on the native enzyme of progressively lowering the solvent buffer pH was monitored by determining the molecular weight by sedimentation equilibrium analysis, the sedimentation coefficient, the frictional coefficient, and the percent alpha-helix content of the enzyme. The alkaline phosphatase dissociates into two subunits around pH 4. At pH 2.8 a further decrease in S value, but no change in molecular weight, is observed, indicating a change in conformation. The frictional coefficients and percent alpha-helix content agree with this interpretation. A subunit molecular weight of 59,000 was calculated from sodium dodecyl sulfate gels.